The Singapore blue chips the rewards & risks of investing in Singapore's largest corporates - Vijayaraghavan, Nandini (World Scientific Publishing Co. Pte Ltd., 2017)
"A pioneering and comprehensive work, The Singapore Blue Chips puts the spotlight on 22 of Singapore's largest corporates. This is the first book that provides a quick snapshot of Singapore's large cap (large market capitalisation) corporates as investment propositions, and is a timely tribute to the nation's 50 years of independence and development. Written for finance professionals and students as well as readers with a general interest in business, investing and finance, each chapter of this book is dedicated to one company and delves into its attractiveness as an investment proposition, the associated investments risk and the company's prospects as of end-2016."--Publisher's website